TRANSPARANSI PENGELOLAAN DANA DESA TAMBANG DALAM MENINGKATKAN INFRASTRUKTUR DI DESA TAMBANG KECAMATAN TAMBANG KABUPATEN KAMPAR TAHUN 2024 - Bakri, Jihan Aulia; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Article 78 of Law Number 6 of 2014 states that the purpose of village development is to improve the welfare of rural communities. Article 1 explains that village funds are used to finance government administration, the implementation of development, community development, and community empowerment. Therefore, the Minister of Finance Regulation (PMK) Number 108 of 2024 regulates the management of Village Funds for the year 2025. In managing village funds, transparency from the village government is needed, starting from the availability and accessibility of documents, clarity and completeness of information, and openness of processes. This research uses a descriptive qualitative research method. The theory used as the basis of this research is the theory of transparency (Kristianten, in M. Fikri 2022) and the Minister of Finance Regulation (PMK) Number 108 of 2024 regulates the management of Village Funds. Based on the research findings, it can be concluded that overall, the Tambang village government is transparent regarding village funds in every activity. In determining the infrastructure to be implemented, the village government holds meetings at the hamlet level, and the results of the hamlet meetings are proposed to the village meeting and then the Village Development Plan (RKPDes) is compiled. The village government is open and invites the community to participate or supervise activities in the Tambang village, such as by putting up banners and reports of activities. Keywords: Transparency, Village Fund Management, Infrastructure